PENGARUH BOKASI MUCUNA SP TERHADAP PERTUMBUUHAN DAN HASIL TANAMAN PETSAI PADA TANAH ALUVIAL - kristianto, wahyudi (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims were to determine the effect of the best dose of Mucuna sp for the growth and yield of Chinese cabbage on alluvial soil. This research was conducted from April 2018 to May 2018 at the Experimental Garden of the Faculty of Agriculture, Tanjungpura University. This study used a Completely Randomized Design (CRD) consisting of 6 treatments with 4 replications and each replication consisted of 4 samples. The treatment were of: 800g / polybag Bocation Mucuna sp; 1,200g / polybag Bocation ;Mucuna Sp, 1,600g / polybag Bocation Mucuna sp;2000g / polybag Bocation Mucuna sp, 2,400g / polybag . Bocation Mucuna sp, 2,800g / polybag Bocation Mucuna Sp. Variables observed in this study were the number of leaves (strands), greenish leaf content (spad unit), leaf area (cm2), root volume (cm3), fresh weight (g), and dry weight (g). The results indieated that opplication statically, there were no significant of Mucunasp various dose used did not increase the growth and yield of Chinese cabbage statically, there were no significant difference a mong treatment. In this a mong the variable observed, its showed that no best dosis of Mucuna sp.Keywords :Aluvial, Bocation Mucuna sp,Mustard petsai